Ductal Carcinoma In Situ Biology, Biomarkers, and Diagnosis - Gorringe, Kylie L.; Fox, Stephen B. (Frontiers in Oncology, 2017)
Ductal carcinoma in situ (DCIS) is a often-diagnosed breast disease and a known, non-obligate, precursor to invasive breast carcinoma. In this review, we explore the clinical and pathological features of DCIS, fundamental elements of DCIS biology including gene expression and genetic events, the relationship of DCIS with recurrence and invasive breast cancer, and the interaction of DCIS with the microenvironment. We also survey how these various elements are being used to solve the clinical conundrum of how to optimally treat a disease that has potential to progress, and yet is also likely over-treated in a significant proportion of cases.